University-organised summer schools as cases of hybrid education - PODERYTĖ, AGNĖ (Journal of Education Culture and Society, 2020)
Aim. The aim of is article is to discuss how summer schools can be approached as instances of hybrid education and how this can help to address the complex needs of their participants living in a culturally and technologically intertwined world.Methodology. This paper analyses the theoretical framework of hybrid education, its manifestations in summer schools and since it needs contextualisation, how it works in a specific case of Baltic Summer University organised by Vytautas Magnus University (Kaunas, Lithuania).Research and conclusion. To reach their target audience, summer schools combine academic content, and the elements of business and entertainment. This results in a separate mode of education with new possibilities and scope, however poses a paradox: while the adoption of business and entertainment practices puts summer schools somewhat outside the realm of the traditional university practices, it makes higher education more approachable and able to react to the fast-changing reality. Baltic Summer University fits the pattern established and as such, could benefit from a more active engagement of this theoretical approach and the opportunities it offers.  Originality. While summer schools are not a particularly new phenomenon, recently this field has witnessed a great expansion in both the supply of programmes and interest from students. The nature of these programmes and sudden interest in them remains under the radar of more extensive in-depth studies, which would actually help to harness its full potential.